Stereoselective production of dimethyl-substituted carbapenams via engineered carbapenem biosynthesis enzymes - Hamed, R; Henry, L; Claridge, T; Schofield, C (American Chemical Society, 2016)
Stereoselective biocatalysis by crotonase superfamily enzymes is exemplified by use of engineered 5-carboxymethylproline synthases (CMPSs) for preparation of functionalized 5-carboxymethylproline (5-CMP) derivatives methylated at two positions (i.e. C2/C6, C3/C6 and C5/C6), including products with a quaternary centre, from appropriately-substituted-amino acid aldehydes and C-2 epimeric methylmalonyl-CoA. The enzymatically-produced disubstituted 5-CMPs were converted by carbapenam synthetase into methylated bicyclic Β-lactams, which manifest improved hydrolytic stability compared to the unsubstituted carbapenams. The results highlight the use of modi-fied carbapenem biosynthesis enzymes for production of new carbapenams with improved properties.